Youth at Risk, Social Exclusion, and Intergenerational Poverty Dynamics: A New Survey Instrument with Application to Brazil - Verner, Dorte (World Bank, Washington, D.C., 2013)
This paper addresses the underlying causes of problems and risks faced by poor and excluded youth of 10-24 years of age. The authors develop a survey instrument that addresses poverty in a broad sense, including hunger, early pregnancy and fatherhood, violence, crime, drug use, low levels of social capital, and low educational attainment. The authors also shed light on intergenerational transfer of risks that are considered to induce poverty. They document findings based on the survey data gathered in three poor urban neighborhoods in Fortaleza in Northeast Brazil. Their main findings show that: (i) Poor youth are at considerable risk of growing up without their father. Only 7 percent grow up with their father present in the household. (ii) The intergenerational transmission of low education attainment is at play, but it is diminishing. (iii) The risk of early pregnancy and fatherhood is large among poor and excluded youth-31 percent of the youth had their first child before age 16, triple that of the adult population. (iv) The risk of sexual abuse and violence within the household exists-6 percent of the youth answered that they had their first sexual relationship with a family member, and 13 percent grow up in households with violence. (v) The social capital levels are low-only 5 percent of the youth and 9 percent of the adults have measurable social capital. (vi) The risk of growing up in a violent neighborhood is large-59 percent of the youth claim that they live in a violent neighborhood, 80 percent feel unsafe in their neighborhood, and 50 percent feel unsafe at home.